Emerging technologies for food preservation - Gelvez Ordoñez, Victor Manuel (Sello Editorial Unipamplona, 2025)
The book addresses a broad spectrum of emerging technologies applied in the food industry, with a special emphasis on non-thermal treatments designed to preserve food quality without compromising its nutritional and organoleptic properties. The main technologies analyzed include cold plasma, magnetic fields, ultrasound, irradiation, and high isostatic pressure. Each technology is studied from its scientific basis and its application in the processing and conservation of food matrices. The analysis covers their effects on physical and chemical properties, with a particular focus on proteins: their functional properties, molecular structure, water retention, oxidative stability, texture, and antimicrobial capacity. Specific aspects are discussed, such as the modification of disulfide bonds, the exposure of hydrophobic groups, and changes in the secondary and tertiary conformation, all of which are crucial for improving the final product’s functional and sensory characteristics. A differential value of the book is the inclusion of results from the authors’ own studies, which enriches the content with updated and specific practical evidence. To complement this, bibliometric studies are presented to evidence the level of global scientific production for each technology, particularly highlighting the prevalence of recent work. This analysis allows the work to be placed in a contemporary and relevant context, showcasing the evolution and current trends in the research of emerging food technologies.